2010
DOI: 10.1098/rsbl.2009.1068
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuating feather asymmetry in relation to corticosterone levels is sex-dependent in Eurasian treecreeper (Certhia familiaris) nestlings

Abstract: Fluctuating asymmetry (FA) has been widely used as a stress-related phenotypic marker of developmental instability. However, previous studies relating FA to various stressful conditions have produced inconsistent results and we still lack quantitative individual-level evidence that high FA is related to stress in wild vertebrate species. We studied how baseline plasma levels of corticosterone predicted FA of wing and tail feathers in free-living Eurasian treecreeper (Certhia familiaris) nestlings. We found a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
(32 reference statements)
1
3
0
Order By: Relevance
“…A similar pattern may be present in protogynous reef fish, where males frequently undergo a period of rapid growth following sex change (Munday et al 2009, Walker andMcCormick 2004). This finding corroborates other studies that detected sex-dependent FA and suggested it was driven by sex-specific growth and energy demands in a species of fly (Bonduriansky 2009) and bird (Helle et al 2010), but an in depth literature review revealed no other studies demonstrating sex-specific FA in otoliths of fishes. As males tended to be more asymmetric than females in this study, greater FA at Wahine Park could be explained by the higher proportion of males to females relative to Kau Bay (Chapter 2).…”
Section: Fluctuating Asymmetry Sex and Sizesupporting
confidence: 90%
See 1 more Smart Citation
“…A similar pattern may be present in protogynous reef fish, where males frequently undergo a period of rapid growth following sex change (Munday et al 2009, Walker andMcCormick 2004). This finding corroborates other studies that detected sex-dependent FA and suggested it was driven by sex-specific growth and energy demands in a species of fly (Bonduriansky 2009) and bird (Helle et al 2010), but an in depth literature review revealed no other studies demonstrating sex-specific FA in otoliths of fishes. As males tended to be more asymmetric than females in this study, greater FA at Wahine Park could be explained by the higher proportion of males to females relative to Kau Bay (Chapter 2).…”
Section: Fluctuating Asymmetry Sex and Sizesupporting
confidence: 90%
“…Studies of FA are problematic because the asymmetry can be expressed in some traits and not others (Blanckenhorn et al 1998, Woods et al 1999 and the magnitude of asymmetry can depend on the type of stress encountered (Campbell et al 1998, Roy andStanton 1999). Furthermore, FA may be reduced in males in populations where females actively select mates (Kodric-brown 1997, Møller 1994 or increased in males due to sex-specific differences in energy demands (Helle et al 2010, Serrano et al 2008. Thus, the ability to detect FA can depend on a thorough understanding of the stress-and sex-specific development of FA in the particular trait examined (Lens et al 2002, Palmer andStrobeck 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, corticosterone or cortisol treatment, either through the mother or directly into the egg, has resulted in increased FA in hatchlings in chickens, Japanese quails and damselfish [23][24][25]. In a free-living species, high corticosterone levels were related to elevated FA levels of male nestlings in tree creepers [26]. These studies-albeit being very relevant as such-were not designed to study maternal stress as the cortisol/corticosterone was administered directly, without challenging the mothers in some way.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of FA are problematic because the asymmetry can be expressed in some traits and not others (Blanckenhorn et al 1998, Woods et al 1999 and the magnitude of asymmetry can depend on the type of stress encountered (Campbell et al 1998, Roy andStanton 1999). Furthermore, FA may be reduced in males in populations where females actively select mates (Kodric-brown 1997, Møller 1994 or increased in males due to sex-specific differences in energy demands (Helle et al 2010, Serrano et al 2008. Thus, the ability to detect FA can depend on a thorough understanding of the stress-and sex-specific development of FA in the particular trait examined (Lens et al 2002, Palmer andStrobeck 2003).…”
Section: Introductionmentioning
confidence: 99%